A New Technique For Domain Delineation Of Rock Mass Discontinuities - Howard R. Hume; Terry R. West; William R. Judd (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
One of the outcomes of a sector slope design in a large open pit in the western United States has been the scrutiny of the structural domain concept. These domains essentially define the area of influence of particular structural characteristics. In the present instance these structural characteristics are joint discontinuities. One of the major drawbacks of defining a domain is that unless large quantities of discontinuity data are available this process of definition is largely qualitative in nature. Viewed from a discontinuity analysis aspect the orientations of all the major joint sets at a given point are a concise descriptor of the structural geologic regime at that location. This is important to domain boundary definition, this in turn is extremely important for assigning which joint sets to use as input for slope stability analysis in a given discontinuity domain. An attempt has been made to develop a quantitative method for defining these discontinuity domains based on limited amounts of orientation data thereby reducing the subjectivity normally involved in such operations. Subjectivity is not always a problem if large quantities of joint orientation data are available, since the mean and variance of joint clusters always can be compared and then grouped to define these domains. However, even this method suffers from the problem that only a single joint set orientation can be considered at a time during the grouping process. On the other hand a discontinuity domain requires that all joint sets at a point be considered simultaneously to truly define the structural discontinuity character of that point. This provides a far more complete